Pengaruh Tenaga Kerja, Tingkat Pendidikan dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi di Kota Medan - A, Azulaidin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine and analyze how much influence the number of workers, education level and government spending have on economic growth in the city of Medan. The hypothesis proposed is that the number of workers, education level and government spending have a positive and significant effect on economic growth in the city of Medan. The type of data used in this study is secondary data. The data is then processed using SPSS 21 with the multiple linear regression analysis method. The results of the study indicate that the number of workers, education level and government spending have a positive effect on economic growth in the city of Medan, the regression results between the dependent variable and the independent variable are R-Square = 0.979 and F statistic = 93.880 so that together the variables of workers, education level and government spending have a positive effect on economic growth in the city of Medan.